The Impact of Ponpes Izzur Risalah in Increasing the Moral Values of the Sipapaga Village Community, Panyabungan Mandailing Natal District - Khofifah Indah Al-Husna Nasution; Puli Taslim Nst (CV. Tripe Konsultan, 2023)
The Izzur Risalah Islamic Boarding School in Sipapaga Village, Panyabungan Mandailing natal District, makes students become leaders and have religious knowledge and is able to encourage the community to improve community moral values. Izzur Risalah Islamic Boarding School, Sipapaga Village, Panyabungan District, has made various efforts to improve the moral values ​​of the people of Sipapaga Village, Panyabungan District, including conducting recitations every night. The background of the study participants varied from the level of occupational profession, age, gender and education. Besides that, the kyai also provide encouragement and provide role models to the community in their daily behavior. Not infrequently the community consults with the kyai when there are religious problems in the community. This study aims to determine the efforts of the Izzur Risalah Islamic Boarding School in increasing the moral values ​​of the people of Sipapaga Village, Panyabungan, Mandailing Natal district. And to find out the impact of the Izzur Risalah Islamic Boarding School in increasing the moral values ​​of the people of Sipapaga Village, Panyabungan, Mandailing Natal district. This research is a descriptive qualitative research. The research sample consisted of 88 households or 15% of the entire population, using a stratified random sampling technique or random samples. Researchers used a qualitative descriptive analysis technique with percentages.